Development of Istima’ Materials Based on a Scientific Approach Using the Audacity Application at SD Islam Cendekia Faiha Palembang - Hidaya, Nur; Wasilah, Wasilah; Sabana, Rendi (Lembaga Penerbitan dan Publikasi Ilmiah Yayasan Pendidikan Tumpuan Bangsa, 2025)
This study aims to develop Istima’ (listening) materials based on the Audacity approach at SD Islam Cendekia Faiha Palembang. The method used is Research and Development (RnD), consisting of stages including needs analysis, design, development, and limited trials. The results from material and media expert validations indicate that the developed materials are highly feasible for use. The use of Audacity facilitates teachers in creating audio materials and enhances student engagement in learning. The resulting Istima’ materials are effective, engaging, and appropriate to the characteristics of elementary school students.